Navezanost in proces separacije-individualizacije pri mladih odraslih v vlogi prostovoljcev na področju psihosocialne pomoči - Kobal, Leonida (Psihološka obzorja (Ljubljana), 2008)
Distinctions among different attachment styles often appear to be unclear. These distinction inadequacies also result from superficial knowledge of psychodynamic factors of the attachment system, which the concept of internal working models often neglects. In my research I have examined the appearance of specific object relations characteristics in the adulthood period. In other words, I have examined the solution of the separation-individuation process according to the internal working models of self and other, which exist in the background of the attachment system. Twenty-one young adult volunteers included in this research took part in a psychotherapeutic camp in order to help children and adolescents with psychosocial problems. Information was gathered with the Interpersonal Relations Questionnaire (Bartholomew in Horowitz, 1991), the Test of Object Relations (Žvelc, 1998) and with two semi-structured interviews. Among volunteers with a negative self-model, dimensions of symbiotic merging, egocentrism, separation anxiety and social isolation were more evident, whereas volunteers with a negative other-model expressed fear of engulfment more clearly. Results have confirmed that volunteers with prevailingly insecure attachment styles have problems with separation-individuation process and with achieving reciprocal autonomy.
Keywords: navezanost; attachment theory; separacija; individualizacija; objektni odnosi; prostovoljno delo; odrasli; prostovoljci